2017
DOI: 10.1186/s40201-017-0277-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations of short-term exposure to air pollution with respiratory hospital admissions in Arak, Iran

Abstract: BackgroundAmbient air pollution, is one of the most frequently stated environmental problems. Many epidemiological studies have documented adverse health effects for ambient air pollution. This study aimed to investigate the association between ambient air pollution and respiratory hospital admissions.MethodsIn this ecological time series study data about air pollutant concentrations including CO, NO2, O3, PM2.5, PM10 and SO2 and, respiratory hospital admissions in the urban population of Arak, from January 1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 52 publications
4
25
3
Order By: Relevance
“…The adverse effects of air pol lution on cardiovascular health have been shown in some observational epidemiological studies. However, there IJOMEH 2018;31(4) 10 from Panama, results showed the effect of PM 10 on cardio vascular deaths in total increases by 5.8% (95% CI: 1.9-9.7) after one month's delay [40]. However, in another study conducted by Braga et al, in 10 US cities, results showed that cardiovascular deaths in contrary to respiratory deaths, which were affected by the level of PM 10 2 days before (time lag 2), were af fected by the level of PM 10 on the same day as well [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adverse effects of air pol lution on cardiovascular health have been shown in some observational epidemiological studies. However, there IJOMEH 2018;31(4) 10 from Panama, results showed the effect of PM 10 on cardio vascular deaths in total increases by 5.8% (95% CI: 1.9-9.7) after one month's delay [40]. However, in another study conducted by Braga et al, in 10 US cities, results showed that cardiovascular deaths in contrary to respiratory deaths, which were affected by the level of PM 10 2 days before (time lag 2), were af fected by the level of PM 10 on the same day as well [43].…”
Section: Discussionmentioning
confidence: 99%
“…There was also a positive rela tion between particulate matter below 10 μm (PM 10 ) and death from coronary heart disease in the ecological study done by Maheswaran et al in Sheffield, England [14]. 10 ), nitrogen dioxide (NO 2 ), carbon monoxide (CO) and sulfur dioxide (SO 2 ). Particulate matter below 10 μm was the only type of par ticulate matter, which had been recorded at the air quality monitoring stations.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A 10 μg/m 3 increase in PM 2.5 corresponds to a 0.68% increase in cardiovascular mortality [4]. Short-term exposure to PM 2.5 induces respiratory hospital admissions [5,6], increases total cerebrovascular disease mortality [7], and even aggravates already diagnosed Parkinson's disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also observed significant effects of O3 on total respiratory disease at some specific lags (124,238,310). For example, in one study conducted in Canada, the authors found respiratory admissions among children aged <3 years old were associated with elevated O3 levels at 2, 3, 4, and 5 days prior to admission with the strongest association observed at a lag of 4 days OR 1.22 (95% CI 1.15 -1.30) based on an increment increase in O3 level of 19 µg/m 3 (124).…”
Section: Discussionmentioning
confidence: 70%